Climate change in the subtropics: the impacts of projected averages and variability on banana productivity - Bergh, I. van den; Ramirez, J; Staver, C; Turner, D.W; Jarvis, A; Brown, D (Acta horticulturae, 2012)
The potential for bananas to produce year round is best expressed when water is abundant and daily temperatures are in the range of 20-30°C. Zones with these conditions produce fruit for the global market. However, banana production, mainly for national markets, has developed in many subtropical areas under less than optimum conditions. Bananas are an important cash crop in southern Brazil, Paraguay and Argentina, in countries of North Africa, the Middle East and southern Africa, and in China and northern India. In these regions, bananas are subject to sub-optimum temperatures and short days. Highly favorable temperatures and long days in the summer may also include short periods of extreme temperatures above 35°C, while rainfall is also highly variable. The effects of climate change on selected subtropical production areas were modeled in a two-step procedure using the EcoCrop model, under current growing conditions and for 2020 and 2050 using a set of 19 IPCC (Intergovernmental Panel on Climate Change) Global Climate Models (GCMs) under the SRES-A2 (business as usual) emission scenario. The modeling showed that current suitability for banana production in the subtropics is much lower than in the tropics with great variation in suitability within the subtropics. Of nine subtropical regions considered, two have improved conditions by 2020s, four are largely unaffected and three have a lower suitability. Our analysis also showed that, in terms of environmental conditions, certain sites are widely represented globally, offering options for technology transfer between sites. Other sites have few similar sites, which means that sites need to be carefully selected for approaches to technology development and transfer. The study leveraged site-specific information with widely available tools to understand potential effects of climate change in the subtropics. However, in order to fully understand the impacts of climate change on banana, the modeling tools used here need to be fully suited for semi-perennial crops to capture the effects of seasonal temperature and rainfall variability on crop cycle length and potential yields.